Correlation of tumor size with Nottingham histological grading among breast cancer patients: a retrospective correlational study - Yuniastini Yuniastini; Yunani Yunani; Sulastri Sulastri; Siti Fatonah; Wien Wiratmoko Guritno Tedjo Prasetio; Prayudi Yushananta (Poltekkes Kemenkes Bandung, 2026)
Background: Tumor size is critical prognostic factor in breast cancer, but evidence regarding its correlation with histological grading is still limited in the Indonesian population. Objective: The aimed of this study was to determine the correlation between tumor size and Nottingham histological grading in breast cancer patients. This study provides the first regional evidence from Lampung, Indonesia, examining the correlation between tumor size and grading using the Nottingham Grading System over 15-year retrospective period (2010–2025). Methods: A descriptive correlational study with a retrospective approach was conducted at RSUDAM, Bandar Lampung, from February to August 2025. Total of 152 breast cancer patients were selected through purposive sampling.Tumor size was categorized as <2 cm, 2–5 cm, and >5 cm based on histopathological examination. Grading was performed using the Nottingham Grading System (grades 1–3). Data were collected from medical records and analyzed using descriptive statistics and Spearman's Rank-Test (α=0.05). Results:The largest tumor size (>5 cm) was found in 44.3% of patients, and grade 3 was the most common (45%). Spearman correlation analysis revealed a statistically significant association between tumor size and histological grading (p=0.046). Among grade 3 tumors, 35.9% were >5 cm, while 75% of grade 1 tumors were 2–5 cm. Overall, a statistically significant negative correlation was observed between tumor grading and tumor size (rₛ = −0.199, p = 0.046). Conclusion: Tumor size correlated significantly with Nottingham histological grading, with larger tumors associated with higher grades, highlighting the need for early detection programs to identify breast cancer at smaller stages and lower grades.